A Multilevel Approach to Relating Subjective Workload to Performance After Shifts in Task Demand. (December 2014) - Mracek, Derek L.; Arsenault, Matthew L.; Day, Eric Anthony; Hardy, Jay H.; Terry, Robert A.
Objective: The aim of this laboratory experiment was to demonstrate how taking a longitudinal, multilevel approach can be used to examine the dynamic relationship between subjective workload and performance over a given period of activity involving shifts in task demand. Background: Subjective workload and conditions of the performance environment are oftentimes examined via cross-sectional designs without distinguishing within- from between-person effects. Given the dynamic nature of performance phenomena, multilevel designs coupled with manipulations of task demand shifts are needed to better model the dynamic relationships between state and trait components of subjective workload and performance. Method: With a sample of 75 college students and a computer game representing a complex decision-making environment, increases and decreases in task demand were counterbalanced and subjective workload and performance were measured concurrently in regular intervals within performance episodes. Data were analyzed using hierarchical linear modeling. Results: Both between- and especially within-person effects were dynamic. Nevertheless, at both levels of analysis, higher subjective workload reflected performance problems, especially more downstream from increases in task demand. Conclusion: As a function of cognitive-energetic processes, shifts in task demand are associated with changes in how subjective workload is related to performance over a given period of activity. Multilevel, longitudinal approaches are useful for distinguishing and examining the dynamic relationships between state and trait components of subjective workload and performance. Application: The findings of this research help to improve the understanding of how a sequence of demands can exceed a performer's capability to respond to further demands.